Sistem Inkubasi Mikroklimat dengan Kendali Proporsional dan Pemantauan IoT untuk Aklimatisasi Bibit Dendrobium - Al Barra Harahap; Vera Khoirunisa; Nauval Abi Sopian; Ahmad Rasya Mahfud (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Dendrobium orchid seedlings transferred from in vitro culture require stable microclimate conditions during acclimatization, particularly temperature, humidity, and photoperiod regulation, to improve adaptation to non-aseptic environments. However, quantitative evaluations of laboratory-scale incubation systems under constrained actuation conditions remain limited. This study presents a compact microclimate incubation system implementing proportional-only temperature control using fan-based unidirectional cooling, scheduled irrigation and lighting, and real-time IoT monitoring through a Node-RED dashboard. The system was developed using an ESP32-S3 controller and DHT22 sensors in a semi-enclosed multi-tier rack with a capacity of 360 seedling pots. Sensor calibration showed strong agreement with a reference instrument, achieving R² > 0.99 for temperature and humidity measurements. Temperature regulation at a reference value of 29.3 °C achieved a steady-state mean absolute error of 0.1 °C within a deviation range of −0.5 to +0.1 °C during 572 minutes of continuous operation, while maintaining all measurements within ±2 °C of the thermal tolerance range for Dendrobium acclimatization. Increasing proportional gain from = 1000 to 2550 reduced the reference entry time from 362 s to 208 s. These findings demonstrate that proportional-only control with constrained cooling actuation can provide stable temperature regulation for compact indoor incubation systems.